Peningkatan Kompetensi Guru Biologi SMA/MA Kabupaten Bojonegoro Melalui Pelatihan Genetika Molekuler: Improving the Competence of Biology Teachers at SMA/MA in Bojonegoro Regency Through Molecular Genetics Training - Sugiharto, Sugiharto; Amin, Muhammad Hilman Fu'adil; Pramudya, Manikya; Hayati, Alfiah; Dewi, Firli Rahma Primula; Manuhara, Yosephine Sri Wulan; Soepriandono, Hari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Molecular Genetics has a positive impact on life. The SMA/MA curriculum has included this material as a mandatory subject for grade 12th. There are obstacles to its implementation due to teachers' lack of understanding and skills. The purpose of the community service program is to improve the competence of SMA/MA teachers in the molecular field, especially those who are members of MGMP Bojonegoro Regency. The activity was conducted on Saturday, August 30, 2025, at the Molecular Genetics Laboratory of the Biology Department, Airlangga University. A total of 25 participants attended this activity, which was coordinated by the Chair and Secretary of MGMP. Participants were given lectures and practicums on the technique of using micropipettes; isolating DNA and measuring its purity; and principles and materials for DNA amplification with PCR and electrophoresis. Referring to program results (1) an increase in highest score range during post-test (range 61-80 = 44%) compared to pre-test (range 21-40 = 60%), (2) highest score achieved by participants (pre-test = 70 is 4%, post-test = 90 is 20%) (3) percentage of increase in participants scores of more than 100% is 52%, (4) participants gave scores on satisfaction index above 95%, it can be concluded that this program can improve competence of Biology teachers at SMA/MA Bojonegoro Regency. This competency improvement is an effort to support the learning process and enhance the quality of education at the SMA/MA level, enabling students to excel in science.